Fluorescent glasses and glass ceramics with high content of cerium and tin
By increasing the content of cerium and tin, glass and glass ceramics that significantly improve fluorescence properties under long-wave ultraviolet light were prepared, which solved the problem of insufficient fluorescence properties of existing materials in this wavelength range, and achieved effective simulation of the fluorescence properties of natural tooth materials, which were suitable for dental restorations.
Patent Information
- Application Number
- CN202411315745.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-20
- Filing Date
- 2024-09-20
- Publication Date
- 2025-03-28
AI Technical Summary
Existing glass and glass ceramics exhibit insufficient fluorescent properties under long-wave ultraviolet light, and cannot effectively simulate the fluorescent properties of natural tooth materials, especially in the range of 380 to 430 nm.
By increasing the content of cerium and tin, glass and glass ceramics were prepared containing 4.0 to 20.0% by weight of cerium and 3.1 to 15.7% by weight of tin, which exhibited clear fluorescence in the range of 380 to 430 nm.
The fluorescent properties of glass and glass ceramics are achieved under long-wave ultraviolet light, allowing them to simulate the fluorescent properties of natural tooth materials in the range of 380 to 430 nm, and are suitable for use in dental restorations.
Smart Images

Figure CN119707281A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to glasses and glass ceramics with high cerium and tin contents, which are particularly suitable for producing dental restorations whose fluorescence properties correspond essentially to those of natural teeth. The invention also relates to a process for producing the glasses and glass ceramics according to the invention, and their use as mixing components and as dental materials, in particular for producing dental restorations. Background Art
[0002] Glass ceramics are used in dentistry due to their good mechanical and optical properties, especially for the manufacture of crowns and small bridges.
[0003] WO 2017 / 032745A1 describes lithium silicate low-quartz glass ceramics for dental use. The glass ceramics may contain colorants and fluorescent agents, which are preferably selected from Bi2O3 and Bi2O5 and inorganic pigments and / or oxides of d and f elements, such as Mn oxides, Fe oxides, Co oxides, Pr oxides, Nd oxides, Tb oxides, Er oxides, Dy oxides, Eu oxides and Yb oxides.
[0004] It is known from EP 3696150 A1 that glasses and glass ceramics which contain 0.05 to 5.0% by weight of europium, calculated as Eu 2 O 3 , impart advantageous fluorescence properties to dental restorations produced from these glasses and glass ceramics.
[0005] It is known from W. Buchalla "Comparative Fluorescence Spectroscopy Shows Differences in Non-Cavitated Enamel Lesions" Caries Res. 2005, 39, 150-156 that natural teeth show bluish-white fluorescence under ultraviolet light in the wavelength range of 400 to 650 nm.
[0006] Rukmani et al., J. Am. Ceram. Soc. 2007, 90, 706-711 describes the influence of V and Mn colorants on the crystallization behavior and optical properties of Ce-doped lithium disilicate glass-ceramics. To prepare the glass-ceramics, a mixture of the starting materials SiO2, ZrO2, Li2CO3, K2CO3, MgCO3 and Al(PO3)3 with CeO2, V2O5 and MnO2 is prepared, the mixture is melted at 1500°C in a platinum crucible, cooled and then subjected to several heat treatments in a tube furnace under air supply.
[0007] EP 3696149A1 describes glasses and glass ceramics containing cerium and tin which fluoresce when excited with light having a wavelength of 366 nm. However, when excited with light having a wavelength of 395 nm, the glasses and glass ceramics do not show any fluorescence.
[0008] It has been shown that the glasses and glass ceramics known from the prior art have insufficient fluorescence properties and do not adequately simulate the fluorescence properties of natural tooth material, in particular at wavelengths of about 380 to 430 nm. In particular, there is a need for glasses and glass ceramics which also exhibit good fluorescence properties, in particular in the long-wave UV range, such as 380 to 430 nm. Light of these wavelengths is often used as "black light" in entertainment venues such as nightclubs. Consequently, dental restorations with insufficient fluorescence properties may be recognizable as restorations under the influence of long-wave UV light, or may be perceived as tooth gaps or defects. Summary of the invention
[0009] The invention is based on the problem of providing glasses and glass ceramics which exhibit a fluorescence comparable to that of natural dental materials and are therefore particularly suitable for producing dental restorations which not only exhibit good mechanical properties but also can largely simulate the fluorescence properties of natural dental materials at excitation wavelengths in the long-wave UV range, such as 380 to 430 nm. The glasses and glass ceramics should also be suitable as mixing components for adjusting the fluorescence properties of other glasses and glass ceramics.
[0010] According to the invention, this problem is solved by the glasses and glass ceramics containing cerium and tin according to the invention and the use of these glasses and glass ceramics according to the invention. The invention also relates to a method according to the invention for producing the glasses and glass ceramics according to the invention and a method according to the invention for producing dental restorations.
[0011] The present invention relates to glasses and glass ceramics containing cerium and tin, characterised in that they comprise the following components:
[0012] Component weight %
[0013] SiO2 48.0 to 75.0
[0014] Li2O 8.0 to 20.5
[0015] Cerium, as CeO2 4.0 to 20.0
[0016] Tin, calculated as SnO: 3.1 to 15.7.
[0017] Surprisingly, it has been shown that the glasses and glass ceramics according to the invention exhibit improved fluorescence properties compared to the prior art, in particular when exposed to ultraviolet light with a wavelength of 380 to 430 nm, such as 395 nm. It has been found that, in the context of the present invention, the use of higher levels of cerium and tin than known in the prior art leads to changes in the fluorescence properties of the glasses and glass ceramics. In particular, it has been shown that by using a higher proportion of cerium and tin, clearly visible fluorescence can be obtained even at excitation wavelengths in the range of 380 to 430 nm. Therefore, the glasses and glass ceramics according to the invention have proven to be particularly suitable for simulating natural tooth material.
[0018] Without being bound by any particular theory, it is hypothesized that using greater amounts of cerium and tin changes the Ce 3+ The fluorescent properties of the ions shift the excitation spectrum so that clear fluorescence can also be perceived in glasses and glass ceramics when excited with light in the wavelength range of 380 to 430 nm, such as 395 nm.
[0019] According to the invention, it is preferred that the glasses and glass ceramics contain 50.0 to 72.0% by weight, in particular 52.0 to 70.1% by weight and particularly preferably 57.0 to 70.1% by weight of SiO 2 .
[0020] It is further preferred that the glasses and glass ceramics contain 9.0 to 19.0% by weight, in particular 10.1 to 18.2% by weight and particularly preferably 10.9 to 17.3% by weight of Li2O.
[0021] Preferably, the glasses and glass ceramics contain 4.3 to 19.0% by weight, in particular 4.7 to 18.5% by weight, more preferably 5.3 to 17.9% by weight, particularly preferably 5.8 to 16.6% by weight and most preferably 6.1 to 16.0% by weight of cerium, calculated as CeO 2 .
[0022] It is further preferred that the glasses and glass ceramics contain 3.4 to 14.9% by weight, in particular 3.7 to 14.5% by weight, more preferably 4.1 to 14.0% by weight, particularly preferably 4.6 to 13.0% by weight and even more preferably 4.7 to 12.6% by weight of tin, calculated as SnO.
[0023] It is also preferred that the molar ratio of cerium calculated as CeO2 to tin calculated as SnO is in the range from 1.5:1 to 1:1.5, in particular from 1.2:1 to 1:1.2, more preferably from 1.1:1 to 1:1.1, and particularly preferably 1.0:1.0.
[0024] In another preferred embodiment, the glass and glass ceramics comprise:
[0025] Component weight %
[0026] SiO2 50.0 to 72.0 wt%
[0027] Li2O 9.0 to 19.0 wt%
[0028] Cerium, as CeO2 4.3 to 19.0 wt % and
[0029] Tin, 3.4 to 14.9 wt % as SnO
[0030] and especially
[0031] SiO2 52.0 to 70.1 wt%
[0032] Li2O 10.1 to 18.2 wt%
[0033] Cerium, 4.7 to 18.5 wt. % calculated as CeO2 and
[0034] Tin, as SnO 3.7 to 14.5 wt%
[0035] And particularly preferred
[0036] SiO2 52.0 to 70.1 wt%
[0037] Li2O 10.1 to 18.2 wt%
[0038] cerium, 5.3 to 17.9 wt. % calculated as CeO2 and
[0039] Tin, as SnO 4.1 to 14.0 wt. %.
[0040] In a specific embodiment, the glass and glass ceramic further comprises terbium. Preferably, the glass and glass ceramic contain 0 to 3.5% by weight, in particular 0 to 2.6% by weight, and particularly preferably 0.1 to 2.6% by weight of terbium, calculated as Tb4O7.
[0041] It is also preferred that the glasses and glass ceramics contain additional alkali metal oxides Me I 2O in an amount of 0 to 11.5% by weight, in particular 1.0 to 10.5% by weight, further preferably 2.0 to 9.3% by weight and particularly preferably 2.0 to 6.0% by weight. The term "additional alkali metal oxide Me I 2O" refers to alkali metal oxides other than Li2O. I2O is particularly selected from Na2O, K2O, Rb2O and / or Cs2O and preferably from Na2O and / or K2O.
[0042] It is further preferred that the glasses and glass ceramics contain 0 to 11.0% by weight, in particular 0 to 9.3% by weight, more preferably 1.0 to 8.0% by weight and particularly preferably 2.5 to 5.0% by weight of K2O.
[0043] Furthermore, it is preferred that the glass and glass ceramic contain 0 to 11.0% by weight, in particular 1.0 to 10.0% by weight, and particularly preferably 2.0 to 8.0% by weight of an oxide of another divalent element Me II O, the term "another oxide of a divalent element Me II O" refers to divalent oxides other than SnO. II O is particularly selected from MgO, CaO, SrO, BaO and / or ZnO. Particularly preferably, the glasses and glass ceramics contain the oxides of the following divalent elements Me in the indicated amounts: II At least one, and in particular all, of O:
[0044] Component weight %
[0045] MgO 0 to 2.0
[0046] CaO 0 to 2.5
[0047] SrO 0 to 4.0
[0048] ZnO 0 to 2.2.
[0049] Furthermore, it is preferred that the glasses and glass ceramics contain 0 to 3.0% by weight, in particular 0 to 1.0% by weight, of BaO and particularly preferably are substantially free of BaO.
[0050] It is also preferred if the glasses and glass ceramics contain 0 to 2.0% by weight, in particular 0 to 1.5% by weight, more preferably 0 to 1.0% by weight and particularly preferably 0.1 to 1.0% by weight of MgO.
[0051] In a further preferred embodiment, the glasses and glass ceramics contain 0 to 2.5% by weight, in particular 0 to 1.8% by weight, more preferably 0 to 1.4% by weight and particularly preferably 0.1 to 1.4% by weight of CaO.
[0052] Furthermore, it is preferred that the glasses and glass ceramics contain 0 to 3.0% by weight, more preferably 0 to 2.8% by weight, in particular 0 to 2.5% by weight and particularly preferably 0.1 to 2.5% by weight of SrO.
[0053] In a preferred embodiment, the glasses and glass ceramics contain 0 to 2.2% by weight, in particular 0 to 1.7% by weight, more preferably 0 to 1.3% by weight and especially preferably 0.1 to 1.3% by weight of ZnO.
[0054] Further preferred are oxides Me containing 0 to 8.0% by weight, in particular 0 to 7.0% by weight, and particularly preferably 2.0 to 6.8% by weight of further trivalent elements. III 2O3 glasses and glass ceramics. The term "oxides of other trivalent elements Me III 2O3" refers to trivalent oxides other than Ce2O3, in which the Me III 2O3 is particularly selected from Al2O3, B2O3, Y2O3, La2O3, Dy2O3, Ga2O3 and / or In2O3, preferably from Al2O3, B2O3, Y2O3 and / or La2O3.
[0055] In a preferred embodiment, the glass and glass ceramic further contain 0 to 8.0% by weight, more preferably 0 to 6.8% by weight, further preferably 1.0 to 6.0% by weight, and particularly preferably 2.0 to 4.0% by weight of Al2O3.
[0056] Furthermore, the glasses and glass ceramics may contain oxides of further tetravalent elements Me IV O2 in an amount of 0 to 2.0% by weight, preferably 0 to 1.5% by weight, in particular 0 to 1.0% by weight and preferably 0.1 to 1.0% by weight. The term "another oxide of a tetravalent element Me IV "O2" refers to tetravalent oxides other than SiO2, CeO2 and SnO2. IV O2 is particularly selected from ZrO2, TiO2 and / or GeO2.
[0057] It is also preferred if the glasses and glass ceramics contain 0 to 2.0% by weight, in particular 0 to 1.5% by weight, more preferably 0 to 1.0% by weight and particularly preferably 0.1 to 1.0% by weight of ZrO 2 .
[0058] In a preferred embodiment, the glass and glass ceramic further comprises an oxide of a pentavalent element Me V 2O 5, The amount thereof is 0 to 8.0% by weight, in particular 0 to 7.0% by weight, preferably 1.0 to 7.0% by weight, more preferably 2.0 to 6.8% by weight, and particularly preferably 3.0 to 6.5% by weight. V2O5 is particularly selected from P2O5, V2O5, Ta2O5 and / or Nb2O5, and particularly preferably from P2O5 and / or Ta2O5. In this context, P2O5 can act in particular as a nucleating agent. However, according to the invention, the presence of a nucleating agent is not absolutely necessary.
[0059] Furthermore, it is preferred that the glass and glass ceramic contain 0 to 8.0% by weight, in particular 0 to 7.0% by weight, more preferably 0 to 6.8% by weight and particularly preferably 1.0 to 6.5% by weight of P2O5.
[0060] Furthermore, the glasses and glass ceramics may contain 0 to 5.0% by weight, in particular 0 to 2.0% by weight, of fluorine.
[0061] It is particularly preferred that the glasses and glass ceramics contain at least one, and preferably all, of the following components in the amounts indicated:
[0062] Component weight %
[0063] SiO2 48.0 to 75.0
[0064] Li2O 8.0 to 20.5
[0065] Cerium, as CeO2 4.0 to 20.0
[0066] Tin, as SnO 3.1 to 15.7
[0067] Me I 2O 0 to 11.5
[0068] Me II O 0 to 11.0
[0069] Me III 2O3 0 to 8.0
[0070] Me IV O2 0 to 2.0
[0071] Me V 2O5 0 to 8.0
[0072] Terbium, as Tb4O7 0 to 3.5
[0073] Fluorine 0 to 5.0,
[0074] Among themMeI 2O, Me II O.Me III 2O3、Me IV O2 and Me V 2O5 has in particular the meaning given above.
[0075] In another preferred embodiment, the glass and glass ceramics comprise at least one, and preferably all, of the following components in the indicated amounts:
[0076] Component weight %
[0077] SiO2 48.0 to 75.0
[0078] Li2O 8.0 to 20.5
[0079] Cerium, as CeO2 4.0 to 20.0
[0080] Tin, as SnO 3.1 to 15.7
[0081] K2O 0 to 11.0
[0082] Al2O3 0 to 8.0
[0083] MgO 0 to 2.0
[0084] CaO 0 to 2.5
[0085] SrO 0 to 4.0
[0086] ZnO 0 to 2.2
[0087] Terbium, as Tb4O7 0 to 3.5
[0088] P2O5 0 to 8.0
[0089] ZrO2 0 to 2.0.
[0090] In another particularly preferred embodiment, the glasses and glass ceramics comprise at least one, and preferably all, of the following components in the amounts indicated:
[0091] Component weight %
[0092] SiO2 52.0 to 70.1
[0093] Li2O 10.1 to 18.2
[0094] Cerium, as CeO2 4.3 to 19.0
[0095] Tin, as SnO 3.4 to 14.9
[0096] K2O 0 to 9.3
[0097] Al2O3 0 to 6.8
[0098] MgO 0 to 1.0
[0099] CaO 0 to 1.4
[0100] SrO 0 to 2.5
[0101] ZnO 0 to 1.3
[0102] Terbium, as Tb4O7 0 to 2.6
[0103] P2O5 0 to 6.1
[0104] ZrO2 0 to 1.0.
[0105] It is further preferred that the glass and glass ceramics in this embodiment contain 4.7 to 18.5 wt. % cerium based on CeO2 and 3.7 to 14.5 wt. % tin based on SnO, in particular 5.3 to 17.9 wt. % cerium based on CeO2 and 4.1 to 14.0 wt. % tin based on SnO, more preferably 5.8 to 16.6 wt. % cerium based on CeO2 and 4.6 to 13.0 wt. % tin based on SnO, and particularly preferably 6.1 to 16.0 wt. % cerium based on CeO2 and 4.7 to 12.6 wt. % tin based on SnO.
[0106] The invention also relates to precursors of corresponding composition from which the glass ceramic according to the invention can be produced by heat treatment. These precursors are glasses of corresponding composition (also called starting glasses) and glasses with cores of corresponding composition. The term "corresponding composition" means that these precursors contain the same components in the same amounts as the glass ceramic, wherein the components except fluorine are calculated as oxides, as is customary for glasses and glass ceramics.
[0107] The invention also relates to a glass according to the invention containing a core for crystallization. By heat treatment of the glass according to the invention, a glass according to the invention with a core can first be produced and then converted into a glass ceramic according to the invention by further heat treatment.
[0108] The invention further relates to a glass according to the invention and a glass ceramic according to the invention which, when excited with light having a wavelength of 380 to 430 nm, in particular 395 nm, exhibits a white-blue fluorescence color in the CIE color space.
[0109] The invention furthermore relates to a method for producing a glass according to the invention or a glass ceramic according to the invention, wherein tin is used at least partly in divalent form, in particular in the form of SnO.
[0110] In the preparation of the glasses and glass ceramics according to the invention, in particular a mixture of suitable starting materials such as carbonates, oxides, phosphates and fluorides is melted. In a preferred embodiment, the starting materials of the components of the glasses and glass ceramics according to the invention are melted at a temperature of 1400 to 1800° C., in particular 1450 to 1600° C., and particularly preferably about 1500° C., for a period of 20 minutes to 10 hours. In order to achieve a particularly high degree of homogeneity, the glass melt obtained is poured into water to form glass particles, and the particles obtained are then remelted.
[0111] The melt can be poured into a mold to produce a blank of the starting glass - a so-called solid glass blank or monolithic blank.
[0112] It is also possible to add the melt to water again to produce granules.The granules can then, after grinding and optionally adding further components such as colorants, be pressed into blanks - so-called powder compacts.
[0113] Finally, the starting glass can also be processed into a powder after granulation.
[0114] The glass, for example in the form of a solid glass blank, a powder compact or a powder, can then be subjected to a heat treatment to produce a glass with a core. This is also referred to as a nucleation process. The invention therefore also relates to a method for preparing a glass with a core, wherein the glass is subjected to a heat treatment at a temperature of 450 to 600° C., and in particular 470 to 550° C., for a duration of in particular 5 to 120 minutes, preferably 10 to 60 minutes.
[0115] The glass with the core can then be used to form the glass ceramic according to the invention by heat treatment. Therefore, the present invention also relates to a method for producing the glass ceramic according to the invention, wherein the glass, in particular the glass with the core, is subjected to at least one heat treatment at a temperature of 700 to 950° C. for a duration of in particular 5 to 120 minutes and preferably 10 to 60 minutes.
[0116] The glass according to the invention and the glass according to the invention having a core are preferably subjected to at least one heat treatment in the form of a powder or a powder compact to produce a glass ceramic.
[0117] In a further preferred embodiment, at least one heat treatment is performed as part of a sintering-on process, in particular a sintering-on process of a powder.
[0118] Therefore, in a preferred embodiment, the present invention relates to a process for producing a glass ceramic according to the invention, wherein
[0119] (a) pressing a powder of the glass according to the invention, optionally after addition of further components such as other glasses, glass ceramics and / or pressing aids, to form a powder compact, and
[0120] (b) subjecting the powder compact to a heat treatment at a temperature of 700 to 950° C., in particular for a period of 5 to 120 minutes.
[0121] In this method, nucleation may optionally be performed prior to the heat treatment in step (b).
[0122] In addition, the present invention relates to the use of the glass according to the invention and the glass ceramic according to the invention with a high content of cerium and tin for adjusting the fluorescence of another glass and another glass ceramic. Therefore, glasses and glass ceramics comprising the glass according to the invention or the glass ceramic according to the invention constitute another subject of the present invention. In this context, particularly preferred are glasses and glass ceramics comprising the glass according to the invention or the glass ceramic according to the invention containing cerium and tin, the amount of the glass according to the invention or the glass ceramic according to the invention containing cerium and tin being 0.1 to 60% by weight, in particular 1 to 58% by weight, preferably 5 to 56% by weight, particularly preferably 10 to 54% by weight, and more preferably 15 to 52% by weight based on the total amount of the glass or glass ceramic and the glass according to the invention or the glass ceramic according to the invention.
[0123] The glasses and glass ceramics according to the invention with a high content of cerium and tin can be used in particular in combination with a variety of other glasses and / or glass ceramics, and these combinations can be used in particular as dental materials. Particularly preferably, the combination can be in the form of a sintered blank. Examples of other glasses and glass ceramics for producing the combination are disclosed in DE 4314817 A1, DE 4423793 C1, DE 4423794 C1, DE 4428839 A1, DE 19647739 A1, DE 19725552 A1, DE10031431 A1, EP 0827 941 A1, EP 0916625 A1, WO 00 / 34196 A2, EP 1505041 A1, EP1688398 A1, EP 2287122 A1, EP 2377831 A1, EP 2407439 A1, WO 2013 / 053863 A2, WO 2013 / 053864 A2, WO 2013 / 053865 A2, WO 2013 / 053866 A2, WO 2013 / 053867 A2, WO 2013 / 053868 A2, WO 2013 / 164256 A1, WO 2014 / 170168 A1, WO 2014 / 170170 A2, WO 2015 / 067643 A1, WO 2015 / 155038 A1, WO 2015 / 173394 A1, WO 2016 / 120146 A1, WO 2017 / 032745 A1, WO 2017 / 055010 A1. These glasses and glass ceramics belong to the group of silicates, borates, phosphates or aluminosilicates. Preferred glasses and glass ceramics are of the SiO2-Al2O3-K2O type (with cubic or tetragonal leucite crystals), SiO2-B2O3-Na2O type, alkali metal silicate type, alkali metal zinc silicate type, silicophosphate type and / or SiO2-ZrO2 type. Particularly preferred are lithium silicate glass ceramics, and in particular glass ceramics containing as main crystalline phase lithium metasilicate or lithium disilicate and optionally further crystalline phases such as lithium metasilicate, lithium disilicate, apatite, diopside, spodumene, petalite, eucryptite and / or wollastonite, and glass ceramics containing SiO2, in particular SiO2 in the form of a low quartz solid solution and / or a high quartz solid solution as main crystalline phase. By mixing such glasses or glass ceramics with glasses and / or glass ceramics according to the invention having a high content of cerium and tin, the fluorescence properties can be adjusted in a desired manner.
[0124] The glasses according to the invention and the glass ceramics according to the invention are present, in particular, in the form of a combination, in particular in the form of a powder, granules, paste, aerosol or blanks of any shape and size, for example, monolithic blanks in unsintered, partially sintered or densely sintered form, such as flakes, cuboids or cylinders, or powder compacts. In these forms, they can be easily further processed, such as into dental restorations. However, they can also be in the form of dental restorations, such as inlays, onlays, crowns, partial crowns, bridges, veneers, facets or abutments, or as coatings for dental restorations.
[0125] Dental restorations such as inlays, onlays, crowns, partial crowns, bridges, veneers, facets or abutments can be produced from the glass ceramics according to the invention and the glasses according to the invention, in particular in combination. The invention therefore relates to their use as dental materials and in particular to their use in the preparation of dental restorations. Preferably, the glass ceramics and glasses are given the shape of the desired dental restoration by pressing, sintering or machining.
[0126] The pressing is usually carried out under high pressure and high temperature. Preferably, the pressing is carried out at a temperature of 700 to 1150° C., and in particular at a temperature of 700 to 1000° C. Further preferably, the pressing is carried out at a pressure of 10 to 30 bar. During the pressing, the desired shape change is achieved by the viscous flow of the material used. The glass according to the invention and the glass with a core according to the invention, and preferably the glass ceramic according to the invention can be used for pressing. In particular, the glass and glass ceramic according to the invention can be used in the form of blanks of any shape and size, such as powder compacts in the form of unsintered, partially sintered or densely sintered forms.
[0127] Machining is usually carried out by material removal methods, and in particular by milling and / or grinding. It is particularly preferred that machining is carried out as part of a CAD / CAM process. Glass according to the invention, glass with a core according to the invention and glass ceramic according to the invention can be used for machining. In this context, glass and glass ceramic according to the invention can be used in particular in the form of blanks, such as unsintered, partially sintered or densely sintered powder compacts. Preferably, glass ceramic according to the invention is used for machining. Glass ceramic according to the invention can also be used in a form that is not yet fully crystallized, which is manufactured by heat treatment at lower temperatures. This provides the advantage of easier machining, and therefore uses simpler equipment for machining. After machining this partially crystallized material, it is usually subjected to further heat treatment to induce further crystallization.
[0128] The glass ceramics according to the invention and the glasses according to the invention, in particular in combination, are also suitable for coating ceramics, glass ceramics and metals, for example. A "coating" that can be produced using the glasses according to the invention and the glass ceramics according to the invention, in particular in combination, also refers to, for example, glazes.
[0129] The invention therefore also relates to the use of the glass according to the invention and the glass ceramic according to the invention, in particular in combination, for coating, in particular, ceramics, glass ceramics and metals. The coating preferably comprises applying the glass according to the invention or the glass ceramic according to the invention, in particular in combination, to a substrate material and subjecting it together with the substrate material to a heat treatment, preferably at a temperature of at least 600° C., in particular from 600 to 1150° C., and particularly preferably from 700 to 1000° C.
[0130] This can be done in particular by firing and preferably by pressing. In the case of firing, the glass ceramics and glasses are applied to the material to be coated, such as ceramics, glass ceramics or metals, in the usual way, such as as powders, pastes or aerosols, and then sintered. In a preferred pressing method, the glass ceramics according to the invention and the glasses according to the invention are pressed as powder compacts at high temperatures of, for example, 700 to 1150° C., and in particular 700 to 1000° C., and under a pressure of, for example, 10 to 30 bar. In particular, the method described in EP 231 773 and the pressing furnace disclosed therein can be used for this purpose. A suitable commercial furnace is a Programat type furnace from Ivoclar Vivadent AG, Liechtenstein.
[0131] Due to the above-mentioned properties of the glass ceramics according to the invention and the glasses according to the invention, they are particularly suitable for use in dentistry. Therefore, the present invention also aims to use the glass ceramics according to the invention and the glasses according to the invention, in particular in combination, as dental materials and in particular for the production of dental restorations or for coating dental restorations, such as crowns, bridges and abutments.
[0132] Particularly preferred is the use for coating dental restorations, wherein a substrate material, in particular a glass ceramic, a ceramic or a metal, is coated with the glass according to the invention or the glass ceramic according to the invention, in particular in combination. Particularly preferably, the dental restoration is selected from the group consisting of inlays, onlays, crowns, partial crowns, bridges, veneers, facets and abutments.
[0133] The use for coating dental restorations preferably comprises applying the glass according to the invention or the glass ceramic according to the invention, in particular in the form of a combination, to a substrate material and subjecting it together with the substrate material to a heat treatment, preferably at a temperature of at least 600° C., in particular from 600 to 1150° C. and particularly preferably from 700 to 1000° C. The application of the glass according to the invention or the glass ceramic according to the invention, in particular in the form of a combination, is carried out in the usual manner, for example as a powder, paste or aerosol.
[0134] The present invention therefore also relates to a method for producing a dental restoration, in particular an inlay, onlay, crown, partial crown, bridge, veneer, facet or abutment, wherein the glass ceramic or glass according to the invention, in particular in combined form, is given the shape of the desired dental restoration by pressing, sintering or machining, in particular as part of a CAD / CAM process.
[0135] The invention also relates to a method for coating a dental restoration, in particular an inlay, onlay, crown, partial crown, bridge, veneer, facet or abutment, wherein a glass according to the invention or a glass ceramic according to the invention, in particular in combination, is applied to a substrate material and subjected together with the substrate material to a heat treatment, preferably at a temperature of at least 600° C., in particular from 600 to 1150° C. and particularly preferably from 700 to 1000° C. The application of the glass according to the invention and the glass ceramic according to the invention, in particular in combination, is carried out in the usual manner, for example as a powder, paste or aerosol. Preferably, the substrate material is a glass ceramic, a ceramic or a metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0137] The present invention will now be described in more detail, by way of example only, with reference to the accompanying drawings, in which:
[0138] Figure 1 The diagram illustrates the fluorescent glass frit of Example 3 (right) and a solid glass sheet (left) produced from the glass frit of Example 31 by carrying out the procedure described in EP 3 696 149 A1 for Example 5 thereof when excited with a UV LED (excitation wavelength 395 nm).
[0139] Figure 2 The diagram shows the fluorescent glass ceramic blank of Example 15 (right side) when excited by a UV LED (excitation wavelength 395 nm) and the Figure 1 The solid glass sheet shown is a non-fluorescent solid glass sheet manufactured by the same method (left side).
[0140] Figure 3The diagram shows the fluorescent glass ceramic blank of Example 17 (right side) when excited by a UV LED (excitation wavelength 395 nm) and the Figure 1 The solid glass sheet shown is a non-fluorescent solid glass sheet manufactured by the same method (left side). DETAILED DESCRIPTION
[0141] The invention is explained in more detail below with the aid of examples, without these examples restricting the invention.
[0142] Example
[0143] 1. Preparation of fluorescent glass
[0144] Thirty glasses according to the invention were prepared having the compositions given in Table I. For this purpose, starting glasses having the compositions given in Table I were first melted from common raw materials at 1500° C. for 60 minutes. Glass frits were prepared by pouring the molten starting glasses into water.
[0145] In addition, two glasses were produced as comparative examples using the corresponding method. The compositions of these glasses are also given in Table I as Examples 31 and 32. Different from the preparation method of the glasses of Examples 1 to 30, the melting for producing Example 31 was carried out at 1650° C. for 240 minutes.
[0146] Also given in Table I are the glass transition temperatures T for the glasses according to the invention. g Determined by DSC (Differential Scanning Calorimetry).
[0147] The fluorescence properties of the glass frit were investigated. To this end, the glass frit was illuminated successively with a mercury vapor lamp (excitation wavelength 366 nm) and with a UVLED (excitation wavelength 395 nm), and the fluorescence was examined in each case with the naked eye.
[0148] For the glass frits of Examples 1 to 30, clear fluorescence was perceived both when excited by a mercury vapor lamp and when excited by a UV LED.
[0149] The glass frit of Example 31 exhibited clearly perceptible fluorescence when illuminated with a mercury vapor lamp (excitation wavelength 366 nm). However, no fluorescence was perceptible when excited with a UV LED (excitation wavelength 395 nm). Examination of the glass frit of Example 32 showed no perceptible fluorescence either when illuminated with a mercury vapor lamp or when illuminated with a UV LED.
[0150] The glass frit according to the invention has an advantageous fluorescence in Figure 1 The diagram in the figure shows the following figure. Figure 1On the right side of the photograph is shown the fluorescent glass frit of Example 3 when excited with a UV LED (excitation wavelength 395 nm). For comparison, a solid glass sheet was prepared from the glass frit of Example 31 by carrying out the procedure described in EP 3 696 149 A1 for Example 5 thereof. The method comprises remelting the glass frit of Example 31 at 1650° C. for 240 minutes. The melt obtained is then poured onto a copper block to produce a solid glass sheet. The solid glass sheet obtained in this way is shown at Figure 1 is on the left side of the photograph and shows no fluorescence.
[0151]
[0152]
[0153]
[0154] 2. Use of fluorescent glass as a mixing component
[0155] The glass frits of Examples 3 and 32 were ground in a zirconia grinder to a particle size of 45 microns. Subsequently, the ground glass frit of Example 3 was added as a mixing component to the non-fluorescent ground glass frit of Example 32 in different amounts (20, 33 and 50 wt % based on the mixture).
[0156] The different powder mixtures were then pressed into powder compacts by means of a hydraulic press at 15 bar for 10 seconds and sintered at 920° C. for 10 minutes.
[0157] After sintering, the fluorescence properties of the sintered powder compacts were investigated with a mercury vapor lamp (excitation wavelength 366 nm) and with a UV LED (excitation wavelength 395 nm). The sintered powder blanks showed clearly perceptible fluorescence both when illuminated with a mercury vapor lamp and with a UV LED. It was found that strong fluorescence can be obtained by using a high proportion of the fluorescent compound component.
[0158] 3. Preparation of Sintered Glass-ceramic Greensheets
[0159] The glass frits of Examples 9, 10, 15 to 18, 20, 21, 29 and 30 were ground in a zirconium oxide grinder to a particle size of 45 μm. The glass powder obtained was pressed into a blank by means of a hydraulic press at 15 bar for 10 seconds and sintered in a sintering furnace at a temperature T 烧结 and hold time t 烧结The glass ceramic blank is sintered under a temperature of 400 °C to form a dense glass ceramic blank. The crystal phase of the glass ceramic blank is determined by X-ray diffraction (XRD) analysis. The quality of the crystal phase can be determined by the Rietveld method. A suitable method for this is described, for example, in the paper "Glasses and glass ceramics in the system MgO-Al2O3-SiO2 with ZrO2 as nucleating agent" by M. Dittmer, University of Jena, 2011.
[0160] The sintering conditions T used to manufacture each glass ceramic blank 烧结 and t 烧结 The determined crystal phases are given in Table II. The term "main crystal phase" refers to the crystal phase having the highest mass proportion among all crystal phases present in the glass-ceramic.
[0161] The fluorescence of the glass ceramic bodies obtained was measured under a mercury vapor lamp (excitation wavelength 366 nm) and a UV LED (excitation wavelength 395 nm). All sintered glass ceramic bodies showed clearly perceptible fluorescence both when irradiated with a mercury vapor lamp and when irradiated with a UV LED.
[0162] Figure 2 and 3 The diagram illustrates the advantageous fluorescence of the glass ceramic blank according to the invention. Figure 2 The right side of the photograph shows the fluorescent glass ceramic blank of Example 15 when excited with a UV LED (excitation wavelength 395 nm). Figure 3 In the right side of the photo, the fluorescent glass ceramic blank of Example 17 is shown when excited by a UV LED (excitation wavelength 395 nm). Figure 2 and 3 In each photo, a non-fluorescent solid glass sheet is shown on the left side of each photo. Figure 1 The solid glass pieces shown are manufactured in the same way.
[0163]
Claims
1. Glass and glass ceramics containing cerium and tin, comprising the following components: Component weight % SiO2 48.0 to 75.0 Li2O 8.0 to 20.5 Cerium, as CeO2 4.0 to 20.0 Tin, calculated as SnO: 3.1 to 15.
7.
2. The glass and glass ceramic according to claim 1, comprising 50.0 to 72.0% by weight, in particular 52.0 to 70.1% by weight and particularly preferably 57.0 to 70.1% by weight of SiO2.
3. Glass and glass ceramics according to claim 1 or 2, comprising 9.0 to 19.0% by weight, in particular 10.1 to 18.2% by weight and particularly preferably 10.9 to 17.3% by weight of Li2O.
4. The glass and glass ceramic according to any one of claims 1 to 3, comprising 4.3 to 19.0 wt. %, preferably 4.7 to 18.5 wt. %, in particular 5.3 to 17.9 wt. %, more preferably 5.8 to 16.6 wt. %, and particularly preferably 6.1 to 16.0 wt. % cerium, calculated as CeO2.
5. The glass and glass ceramic according to any one of claims 1 to 4, comprising 3.4 to 14.9% by weight, preferably 3.7 to 14.5% by weight, in particular 4.1 to 14.0% by weight, more preferably 4.6 to 13.0% by weight and particularly preferably 4.7 to 12.6% by weight of tin, calculated as SnO.
6. The glass and glass ceramic according to any one of claims 1 to 5, wherein: The molar ratio of cerium, calculated as CeO 2 , to tin, calculated as SnO, is in the range from 1.5:1 to 1:1.5, preferably from 1.2:1 to 1:1.2, in particular from 1.1:1 to 1:1.1, and particularly preferably from 1.0:1.
0.
7. Glass and glass ceramics according to any one of claims 1 to 6, comprising at least one, and preferably all, of the following components in the indicated amounts: Component weight % SiO2 48.0 to 75.0 Li2O 8.0 to 20.5 Cerium, as CeO2 4.0 to 20.0 Tin, as SnO 3.1 to 15.7 Me I 2O 0 to 11.5 Me II O 0 to 11.0 Me III 2O3 0 to 8.0 Me IV O2 0 to 2.0 Me V 2O5 0 to 8.0 Terbium, as Tb4O7 0 to 3.5 Fluorine 0 to 5.0, in Me I 2O is particularly selected from Na2O, K2O, Rb2O and / or Cs2O, Me II O is especially selected from MgO, CaO, SrO, BaO and / or ZnO, Me III 2O3 is particularly selected from B2O3, Y2O3, La2O3, Ga2O3 and / or In2O3, Me IV O2 is particularly selected from ZrO2, TiO2 and / or GeO2, Me V 2O5 is particularly selected from P2O5, V2O5, Ta2O5 and / or Nb2O5.
8. Glass and glass ceramics according to any one of claims 1 to 7, comprising at least one, and preferably all, of the following components in the indicated amounts: Component weight % SiO2 48.0 to 75.0 Li2O 8.0 to 20.5 Cerium, as CeO2 4.0 to 20.0 Tin, as SnO 3.1 to 15.7 K2O 0 to 11.0 Al2O3 0 to 8.0 MgO 0 to 2.0 CaO 0 to 2.5 SrO 0 to 4.0 ZnO 0 to 2.2 Terbium, as Tb4O7 0 to 3.5 P2O5 0 to 8.0 ZrO2 0 to 2.
0. 9 . The glass according to claim 1 , comprising nuclei for crystallization.
10. Glass and glass ceramics, which preferably contain the cerium- and tin-containing glass or glass ceramic according to any one of claims 1 to 9 in an amount of 0.1 to 60% by weight, in particular 1 to 58% by weight, preferably 5 to 56% by weight, particularly preferably 10 to 54% by weight and more preferably 15 to 52% by weight.
11. The glass and glass ceramic according to any one of claims 1 to 10, wherein: The glasses and glass ceramics are in the form of powders, granules, pastes, aerosols, blanks, dental restorations or coatings for dental restorations.
12. A method for preparing a glass or glass ceramic according to any one of claims 1 to 11, wherein: The tin is used at least partly in divalent form, in particular in the form of SnO.
13. The method according to claim 12, wherein: The starting materials of the components of the glass or glass ceramic are melted at a temperature of 1400° C. to 1800° C., in particular 1450° C. to 1600° C., and particularly preferably about 1500° C., preferably for 20 minutes to 10 hours. 14 . Use of the glass or glass ceramic according to claim 1 as a mixing component for adjusting the fluorescence of a glass or glass ceramic.
15. Use of the glass or glass ceramic according to any one of claims 1 to 11 as a dental material, in particular for producing or coating dental restorations.
16. Method for producing a dental restoration, in particular an inlay, onlay, crown, partial crown, bridge, veneer, facet or abutment, wherein the glass or glass ceramic according to any of claims 1 to 11 is given the shape of the desired dental restoration by pressing, sintering or machining, in particular as part of a CAD / CAM process.
Citation Information
Patent Citations
Potassium-zinc silicate glass used in the production of a dental molded product contains oxides of silicon, lithium, potassium and zinc
DE10031431A1
sinterable lithium disilicate glass-ceramic and glass
DE19647739A1
alkali silicate glass
DE19725552A1
opalescent glass
DE4314817A1
leucite-containing phosphosilicate glass ceramics, processes for their production and their use
DE4423793C1